Second Report of Chronic Granulomatous Disease in Jordan: Clinical and Genetic Description of 31 Patients From 21 Different Families, Including Families From Lybia and Iraq - Bakri, Faris Ghalib; Mollin, Michelle; Beaumel, Sylvain; Vigne, Bénédicte; Roux-Buisson, Nathalie; Al-Wahadneh, Adel Mohammed; Alzyoud, Raed Mohammed; Hayajneh, Wail Ahmad; Daoud, Ammar Khaled; Shukair, Mohammed Elian Abu; Karadshe, Mansour Fuad; Sarhan, Mahmoud Mohammad; et al. (Frontiers in Immunology, 2021)
Chronic granulomatous Disease (CGD) is a rare innate immunodeficiency disorder caused by mutations in 1 of the 5 genes (CYBA, CYBB, NCF1, NCF2, and NCF4) encoding the superoxide producing nicotinamide adenine dinucleotide phosphate (NADPH) – oxidase complex in phagocytes. In western population, the most prevalent form of CGD is the X-linked form (XCGD) caused by mutations in CYBB and the autosomal recessive forms (ARCGD) due to mutations in the other genes, collectively account for one-third of CGD cases. We investigated the clinical and molecular features of 22 Jordanian, 7 Libyan, and 2 Iraqi CGD patients from 21 different families. In addition, 11 sibling patients from these families were suspected to die from CGD as suggested by their familial and clinical history. All the patients except 9 were children of consanguineous parents. Most of the patients suffered from ARCGD with mutations in CYBA, NCF1, and NCF2 encoding p22phox, p47phox, and p67phox proteins, respectively. ARCGD was the most frequent form in Jordan probably because consanguineous marriages are common in this country. Only one patient from non-consanguineous parents suffered from an X910CGD subtype. AR670 CGD and AR220 CGD appeared to be the most frequent sub-type but also the most severe clinical forms compared to AR470CGD. As a geographical clustering of 11 patients from 8 Jordanian families exhibited the c.117181175delAAGCT mutation in NCF2, segregating analysis using 9 polymorphic markers overlapping NCF2 permitted to determine that a common ancestor have arisen approximately 1075 years ago between the patients sharing the same haplotype.